Spatial distribution and risk assessment of microplastics in surface sediments in semi-enclosed waters: a case study of Laizhou Bay - Xuzhen Zhang; Hongxian Chu; Meiling Yin; Yadong Liu; Peng Chen; Qiangqiang Zhang; Xuejian Dai; Linghao Kong (Frontiers in Marine Science, 2025)
Marine ecosystems are the most important sinks for microplastics (MPs) from inland sources, and the input of large quantities of MPs into the oceans poses a serious threat to marine organisms and ecosystems. However, the characteristics of MPs contamination and its risk in semi-enclosed seas remain poorly understood. In this research, we conducted a comprehensive analysis and evaluation of the distribution patterns and ecological risks related to MPs found in the surface sediments of Laizhou Bay. We gathered surface sediments from various locations within the bay, which were then processed and analyzed to assess the MP content. According to the results, MPs in Laizhou Bay were widely distributed, with abundances ranging from 36–2125.5 items/g d.w. at different points, with an average of 534.7 items/g d.w. The MP forms were mainly fragments (61.91%) and particles (37.45%), with polyamide (PA) (32.73%), polyethylene terephthalate (PET) (12.42%), and polyurethane (PU) (10.81%) being the most dominant polymer types. MPs mainly originated from marine aquaculture, fishing, and domestic plastic waste; the contribution from marine activities was higher than that from land-based inputs, and their migration and dispersion were mainly affected by the hydrodynamics of water body exchange and intra-bay circulation. According to the pollution load index, the risk index of MPs in Laizhou Bay ranged from 1 to 7.68, indicating a low pollution level. However, the polymer risk index indicated that microplastic pollution in Laizhou Bay was at high risk, and PU and polyvinyl chloride were identified as the primary high-risk sources. This study systematically analyzed the composition, distribution, and multiple source characteristics of MPs in Laizhou Bay. The ecological risks associated with these MPs were assessed through the analysis of pollution load and polymer risk indices. This research offers a valuable dataset and a scientific foundation for understanding and managing MP pollution in semi-enclosed marine environments.